Developing a patient-centered measure to assess food-related and nutrition-related quality of life in patients with cancer - Seth Berkowitz; Mackenzie Kemp; Sara Beachy; Karla Martin; Brooke Worster; Richard W Hass; Iyaniwura Olarewaju; Kristin L Rising (BMJ Nutrition, Prevention & Health)
Background Malnutrition and food insecurity are common challenges among patients with cancer. Nutrition interventions can support patient nutrition needs and quality of life during cancer treatment, though measures to assess impact of interventions are lacking. In prior work, our team developed a Nutrition Experience Survey to assess patient-important domains related to impact of nutrition interventions during cancer treatment, from which a 9-item food-related and nutrition-related quality-of-life (FN-QoL) measure emerged. In this work, we report results from administering the overall Nutrition Experience Survey, including the FN-QoL measure, to a sample of patients with cancer and present initial validity testing of the FN-QoL measure.Methods This is a cross-sectional survey study in which we administered the Nutrition Experience Survey to a convenience sample of English-speaking patients with cancer in Philadelphia, Pennsylvania. Survey responses were summarised with descriptive statistics. Validity and internal consistency of the FN-QoL measure were evaluated with bivariate correlation matrices and Cronbach’s alpha followed by a multiple linear regression analysis.Results 117 individuals completed the survey: mean age 62 (21–90), 49.6% white, 58.3% women. Cronbach’s alpha confirmed adequate internal consistency (0.856) for the FN-QoL. The bivariate correlation matrix indicated that the FN-QoL was correlated with items as expected (eg, poorer subject health ratings, r=−0.48, p<0.001 and nutrition self-efficacy, r=0.38, p<0.05). Multiple linear regression found that receipt of medically tailored meals and treatment-related symptoms were related to FN-QoL when adjusting for all other variables.Conclusion Results suggest validity and potential utility of the FN-QoL measure to assess impact of food and nutrition interventions on quality of life among patients with cancer. Future work should assess applicability of this tool across populations who do not have cancer and sensitivity of this measure to change over time related to receipt of nutrition interventions.